Social Media and Identity Formation: Content Analysis of Movie “Eighth Grade” - Herawati Herawati; Rustono Farady Marta; Hana Rochani G. Panggabean; Changsong Wang (The Journal of Society and Media, 2021)
Movie is regarded as a visual medium that offers a comprehensive presentation of a phenomenon in a defined time. This study employed a qualitative method to provide an interpretive paradigm on the movie titled “Eighth Grade” (directed by Bo Burnham, 2018). It aims to understand the massive role of the use of social media in shaping the identity of young people. The content analysis of movie “Eighth Grade” was carried out by considering abstraction, explication, and structuring. To understand this phenomenon, this study employed Luyckx's perspective on identity formation theory and the social identity model of deindividuation effect. The results of the research showed that the movie "Eighth Grade" vividly described the process of identity formation in a sequential and comprehensive manner, as well as showcased the occurrence of deindividuation processes in social media activities. It Is suggested that to construct a healthy identity, digital activities should complement offline activities, not replace them.